ANTIBACTERIAL ACTIVITY OF CHITOSAN FROM HARUAN (Channa striata) FISH SCALES AGAINST THE GROWTH OF Porphyromonas gingivalis - Rahma Dania A.J; Deby Kania Tri Putri; Irham Taufiqurrahman (FKG Unlam, 2020)
Background: Periodontal disease is one of the dental and oral diseases that is often found in people in Indonesia. RISKESDAS (2018) stated that the prevalence of people who have dental and oral health problems in Indonesia is 57.6%. The prevalence of oral and dental problems in South Kalimantan is 60%. Periodontal disease is damage to the supporting tissues of the teeth caused by specific microorganisms such as Porphyromonas gingivalis which are gram negative bacteria. The growth of these bacteria can be inhibited and killed by chitosan from haruan fish scales. Chitosan is a natural product of chitin, chitosan is the basic ingredient of fish scales. Chitosan has advantages and more safety levels, because it has an active group that will bind to microbes so chitosan can inhibit and kill microbial growth. Objective: to analyze the antibacterial activity of chitosan scales (Channa striata) on the growth of Porphyromonas gingivalis. Methods: This research used true experimental with randomized pre and post test with only control group design with eight treatments. Chitosan of haruan fish scales with liquid dilution method to obtain MIC and solid dilution test to obtain MBC. Results: The results showed that Minimum Inhibitory Concentration (MIC) of chitosan haruan scales was found at a concentration of 2.5% characterized by a decrease in absorbance value of 0.092 and Minimum Bactericidal Concentration found at a concentration of 20% characterized by the absence of Porphyromonas gingivalis. Conclusion: There is an inhibitory activity and a bactericidal activity from chitosan of haruan fish scales on Porphyromonas gingivalis.